Manajemen Pengelolaan Produksi Tahu dalam Meningkatkan Pendapatan Ekonomi Keluarga - Alan Walansari; Wawan Kurniawan; Agus Koni (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Tofu is a food that is widely consumed by Indonesian people. The tofu making business is one of the businesses that is quite promising for increasing family income. Good production management will greatly influence the success of the tofu making business. Good production management must pay attention to several factors, namely planning, organizing, implementing and controlling. The business of making tofu must be carried out by applying the principles of Islamic Economics, namely: Principles of Benefit, Responsible Trust, Honesty and Justice. This research aims to determine the management of tofu production in increasing family economic income. This research uses a qualitative research method with a case study approach. The research results show that good management of tofu production can increase family income. Good tofu production management must pay attention to several factors, namely planning, organizing, action and control.